Nested sensitive periods: how plasticity across the microbiota-gut-brain axis interacts to affect the development of learning and memory. (December 2020) - Callaghan, Bridget
Highlights: A developmental sensitive period in learning and memory results in the unique behaviors of infantile amnesia and relapse-resistant extinction. A developmental sensitive period in the microbiota-gut-brain (MGB) axis exists, which overlaps that seen in learning and memory circuits. The functioning of the MGB axis (and the microbiota specifically) influence learning and memory outcomes during the sensitive period. Longitudinal approaches, measuring multiple biological systems, are required to understand complex learning and memory behaviors. Abstract : There is a growing appreciation for the range of sensitive periods which occur across the brain. These sensitive periods give rise to sensory outcomes, as well as complex higher-order cognitive functions like learning and memory. More recently, an understanding that sensitive periods of development occur outside of the central nervous system (e.g. in the gastrointestinal microbiota) has emerged. Less well understood is how these peripheral sensitive periods may interact with those operating centrally to influence complex behavior. The goal of this paper is to put forward the view that sensitive periods of development occur across the entirety of the microbiota-gut-brain (MGB) axis, and that these nested sensitive periods may interact to influence learning and memory outcomes. Adopting this framework should promote a 'new wave' of thinking in the field which appreciates the complex central and peripheral forces acting on behavior, and uses that understanding to innovate therapies and interventions for disordered learning and memory systems.